The role of Islamic education teacher to build learners' character at MTs Assalafiyah Tegal City - Amalia, Riska (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
The importance of Islamic education teachers' role in building students' character in modern era is reflected on becoming role model who could build students having Islamic character through exemplary and habituation. This research focuses on Islamic education teachers in building students characters at MTs Assalafiyah Tegal city. Thus, it can be drawn problem statements as follow: (1) what is the definition of Islamic education teachers' role? (2) what is definition of character education? (3) How are role of Islamic teachers in building students' characters at MTs Assalafiyah Tegal city? This research used qualitative method especially case study which applied descriptive method to analyze. It was conducted at MTs Assalafiyah Tegalcity. The research subject were the headmaster, teachers and students of class IX. It applied observation, interview, and documentation as the technique of collecting data. It applied data triangulation to analyze the data. The research finds that teachers' role in building students' character at MTs Assalafiyah is categorized as good. It can be seen from MTs Assalafiyah teachers' education background that most of them graduated from Islamic Boarding Schools and Islamic Universities. Teachers have applied their role as the role model in habituating disciplines in their daily life that is crucial to shape students' characters.